Compact and flexible harmonic generator and three-color synthesizer for femtosecond coherent control and time-resolved studies - Burger, C.; Frisch, W. F.; Kardas, T. M.; Trubetskov, Michael K; Pervak, V.; Moshammer, R.; Bergues, B.; Kling, Matthias Friedrich; Wnuk, P. (Optics Express, 2017)
Intense, multi-color laser fields permit the control of the ionization of atoms and the steering of electron dynamics. Here, we present the e cient collinear creation of the second and third harmonic of a 790 nm femtosecond laser followed by a versatile field synthesizer for the three color fields’ composition. Using the device, we investigate the strong-field ionization of neon by fields composed of the fundamental, and the second or third harmonic. The three-color device o ers su cient flexibility for the coherent control of strong-field processes and for time-resolved pump-probe studies.
CRIS-Team Scopus Importer:2023-04-20